Analisis Modelling Mustahiq dalam Pembentukan Akhlak Santri di Pesantren Haji Ya'qub Lirboyo Kota Kediri - Pebriansyah; Uswatun Hasanah (Universitas Islam Tribakti Lirboyo Kediri, 2020)
The focus of this research is the process of shaping the morals of students through modeling carried out by Mustahiq PP.Haji Ya'qub Lirboyo Kediri City. This research is qualitative with the type of phenomenological research. The primary data sources were 3 PPHY students with data collection in the form of in-depth interviews, observation and documentation which were then analyzed with modeling theory. The result was that mustahiq's role as a teacher was able to form perceptions, become a symbol in processing fiber students' emotional intelligence as a motivator. In the end, mustahiq became the role model of the santri.